The right of private defense against non-accountable offenders and in defense of the chastity of women under Islamic law - Owaydhah, Khalid A.; Mohd Yunus, Mohamad Ismail (IIUM Press, International Islamic University Malaysia, 2017)
The right of self-defense under Islamic law (Shariah) distinguishes between two concepts: private and public defense. In this article, legal and practical manifestations of the contemporary legal issue of private defense in the case of physical assaults made by non-accountable (mukallaf) offenders, such as minors and insane persons are focused. Aside from that, this article also analyses the use of private defense to protect the chastity of a woman. The four conditions to exercise the right of private defense are highlighted. In order to explore the effects of private defense, the significance of keeping the lawful measures and exceeding the right of self-defense are also discussed.